Social Media Success for Academic Knowledge Sharing in Indonesia (Conceptual Model Development) - Setiawan Assegaff (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
The aim of this study is to investigate how success is the social media as a tool for knowledge sharing among scholars in Indonesia. To evaluate the success of social media we develop a model base on Delone and McLeane IS Success Model. In this article, we would like discuss the process of developing the research model. In developing the model, we conduct literature review from knowledge management, social media and IS Success Model area from previous study. This study resulted in the social success model for academic knowledge sharing in Indonesia.The aim of this study is to investigate how success is the social media as a tool for knowledge sharing among scholars in Indonesia. To evaluate the success of social media we develop a model base on Delone and McLeane IS Success Model. In this article, we would like discuss the process of developing the research model. In developing the model, we conduct literature review from knowledge management, social media and IS Success Model area from previous study. This study resulted in the social success model for academic knowledge sharing in Indonesia.The aim of this study is to investigate how success is the social media as a tool for knowledge sharing among scholars in Indonesia. To evaluate the success of social media we develop a model base on Delone and McLeane IS Success Model. In this article, we would like discuss the process of developing the research model. In developing the model, we conduct literature review from knowledge management, social media and IS Success Model area from previous study. This study resulted in the social success model for academic knowledge sharing in Indonesia.